Implementation of Zero Trust Architecture for Securing Enterprise Networks - Fajar Hidayat (Global Science: Journal of Information Technology and Computer Science, 2025)
As cyber threats grow more complex, traditional perimeter-based security models are no longer sufficient to protect enterprise networks. This study explores the implementation of Zero Trust Architecture (ZTA) in a mid-sized enterprise network. ZTA emphasizes continuous authentication, least-privilege access, and strict identity verification across all layers of the system. The study used a combination of identity management systems, micro-segmentation, and endpoint verification tools such as Okta, Cisco Duo, and VMware NSX-T. Performance metrics included authentication latency, access control policy enforcement time, and threat detection accuracy. Results showed a 45% improvement in threat containment time and a 60% reduction in lateral movement within the network. The adoption of ZTA also improved compliance with ISO/IEC 27001 standards. This research supports the growing relevance of ZTA in modern IT infrastructures and offers a practical deployment roadmap for organizations seeking to transition from legacy systems to a more resilient cybersecurity posture.